Dominant Negative ATM Mutations in Breast Cancer Families - Chenevix-Trench, Georgia; Spurdle, Amanda B.; Gatei, Magtouf; Kelly, Helena; Marsh, Anna; Chen, Xiaoqing; Donn, Karen; Cummings, Margaret; Nyholt, Dale; Jenkins, Mark A.; Scott, Clare; Pupo, Gulietta M.; et al. (JNCI : Journal of the National Cancer Institute, 2002)
Background: The ATM gene encoding a putative protein kinase is mutated in ataxia-telangiectasia (A-T), an autosomal recessive disorder with a predisposition for cancer. Studies of A-T families suggest that female heterozygotes have an increased risk of breast cancer compared with noncarriers. However, neither linkage analyses nor mutation studies have provided supporting evidence for a role of ATM in breast cancer predisposition. Nevertheless, two recurrent ATM mutations, T7271G and IVS10–6T→G, reportedly increase the risk of breast cancer. We examined these two ATM mutations in a population-based, case–control series of breast cancer families and multiple-case breast cancer families. Methods: Five hundred twenty-five or 262 case patients with breast cancer and 381 or 68 control subjects, respectively, were genotyped for the T7271G and IVS10–6T→G ATM mutations, as were index patients from 76 non-BRCA1/2 multiple-case breast cancer families. Linkage and penetrance were analyzed. ATM protein expression and kinase activity were analyzed in lymphoblastoid cell lines from mutation carriers. All statistical tests were two-sided. Results: In case and control subjects unselected for family history of breast cancer, one case patient had the T7271G mutation, and none had the IVS10–6T→G mutation. In three multiple-case families, one of these two mutations segregated with breast cancer. The estimated average penetrance of the mutations was 60% (95% confidence interval [CI] = 32% to 90%) to age 70 years, equivalent to a 15.7-fold (95% CI = 6.4-fold to 38.0-fold) increased relative risk compared with that of the general population. Expression and activity analyses of ATM in heterozygous cell lines indicated that both mutations are dominant negative. Conclusion: At least two ATM mutations are associated with a sufficiently high risk of breast cancer to be found in multiple-case breast cancer families. Full mutation analysis of the ATM gene in such families could help clarify the role of ATM in breast cancer susceptibility.